Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1007/s00431-018-3207-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a community-based childhood obesity intervention program on changes in anthropometric variables, incidence of obesity, and lifestyle choices in Spanish children aged 8 to 10 years

Abstract: The TCHP did not improve weight development, diet quality, and physical activity in the short term. What is Known: • There is inconsistent evidence for the efficacy of school-based childhood obesity prevention programs. • There is little evidence on the efficacy of childhood obesity intervention programs in other settings. What is New: • This paper contributes information about the efficacy of a multisetting and multistrategy Community Based Intervention (CBI) program that uses the municipality as its unit of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 45 publications
1
39
1
Order By: Relevance
“…Thus, a decrease in both BMI and WC, indicative of abdominal fat distribution, were observed. These findings are different than those from Gomez et al [23] who reported that two academic years' worth of a community-based intervention program reported no significant differences in terms of weight development, obesity incidence or changes in diet quality. These differences could be attributed to the need for a longer follow-up period to observe improvements in terms of body composition of the childhood.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Thus, a decrease in both BMI and WC, indicative of abdominal fat distribution, were observed. These findings are different than those from Gomez et al [23] who reported that two academic years' worth of a community-based intervention program reported no significant differences in terms of weight development, obesity incidence or changes in diet quality. These differences could be attributed to the need for a longer follow-up period to observe improvements in terms of body composition of the childhood.…”
Section: Discussioncontrasting
confidence: 99%
“…For example, results from the Fleurbaix Laventie Ville Santé study carried out in France revealed that the implemented community-based intervention program led to less weight gain in the intervention towns than in the control town [22]. However, results of Gomez et al [23] showed that these kind of programs do not improve weight development, diet quality and physical activity in the short term. Therefore, the aim of our study was to evaluate the effect of a community-based intervention program on the anthropometric measurements and indices in a large and standardized cohort of Spanish children, and to analyze the relative contribution of the school type, as a marker of the socioeconomic status, in overweight and obesity prevalence and trends.…”
Section: Introductionmentioning
confidence: 99%
“…We focused the report on 27 articles as shown in the PRIMA diagram [ 25 - 51 ]; 13 of these studies were carried out in Spain [ 26 - 28 , 33 , 35 , 38 , 41 , 44 - 46, 48, 49, 51 ], 3 studies were carried out in the USA [ 25 , 31 , 47 ], 3 studies were carried out in Italy [ 30 , 36 , 40 ], 4 studies were carried out in other European Union countries [ 32 , 34 , 39 , 50 ] and 4 studies were carried out in Australia [ 29 , 37 , 42 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Gomez et al . [ 33 ] employed the Thao-Child Health Program (TCHP), defined as a community-based intervention for healthy weight development and lifestyle choices, involving 2086 school-aged children. The program included seminars on eating habits and cooking techniques, physical activity, conferences, sport community days, etc., compared to the usual health policy for the control group.…”
Section: Resultsmentioning
confidence: 99%
“…However, community-based programs have yielded mixed findings [ 134 ]. After reporting null results on anthropometric indices of adiposity from a two-school-year, community-based healthy lifestyle program conducted in four Spanish cities (children aged 8–10 years), Gómez et al discussed the limitations that could have contributed to the findings [ 135 ]. According to the authors, the young age of participants, length of follow-up, intervention components, and inability to change the environment and current policies were determinant factors that should be addressed in future investigations [ 135 ].…”
Section: Adipose Tissue Developmentmentioning
confidence: 99%